Preparation of Ferrocene‐Terminated Dendrimers for the Thermal Decomposition of Ammonium Perchlorate - Liu, Jinyi; Yu, Haojie; Wang, Li; Chen, Tao; Vatsadze, Sergey Z.; Chen, Dingning; Shen, Di; Wang, Yu (Macromolecular rapid communications., 2023)
As a common oxidizer, ammonium perchlorate (AP) is an important component in composite solid propellants (CSPs). Ferrocene (Fc)‐based compounds are often selected as burning rate catalysts (BRCs) to catalyze AP decomposition owing to their excellent catalytic behavior. However, one of the drawbacks of Fc‐based BRCs is migration in CSPs. In this study, five Fc‐terminated dendrimers are designed and synthesized to improve the anti‐migration properties, and their chemical structures are confirmed systemically by the related spectra characterization techniques. Moreover, the redox performance, catalytic effect on AP decomposition, combustion performance, and mechanical properties in CSPs are also studied. The shapes of the prepared propellant samples are observed via scanning electron microscopy. The obtained Fc‐based BRCs have good redox performance, a positive effect on promoting AP decomposition, excellent combustion catalytic performance, and good mechanical properties. Meanwhile, they have a higher anti‐migration ability than catocene (Cat) and Fc. This study demonstrates that Fc‐terminated dendrimers have great potential to be applied as anti‐migration BRCs in CSPs. A series of ferrocene (Fc)‐based dendrimers as combustion catalysts are designed and synthesized to enhance the combustion performance of propellants. The final results show that the anti‐migration ability of catalysts is improved a lot and the pyrolysis temperature of AP is reduced greatly. Meanwhile, the burning rate of propellants is improved and the combustion pressure index is reduced greatly.